2019
DOI: 10.1088/1757-899x/655/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of powder bed preheating on distortion and mechanical properties in high speed selective laser melting

Abstract: Selective Laser Melting (SLM) is known to cause residual stresses due to the inherent large thermal gradients from high heating and cooling rates during manufacturing. The residual stresses tend to induce distortion, delamination of parts from the base plate as well as cracking because they reduce the threshold flaw size required for crack initiation. These challenges form a barrier to the use of this additive manufacturing method for structural applications for the aerospace industry where high part integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…High preheating temperature appeared to be more effective for DED compared to selective laser melting (SLM) [ 26 , 27 , 28 ]. Corbin et al studied the influence of Ti-6AL-4V substrate thickness on part distortion at 300 °C preheating and reported that preheating on the thin base plate was more effective [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…High preheating temperature appeared to be more effective for DED compared to selective laser melting (SLM) [ 26 , 27 , 28 ]. Corbin et al studied the influence of Ti-6AL-4V substrate thickness on part distortion at 300 °C preheating and reported that preheating on the thin base plate was more effective [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laser fabrication methods can expose the initial powder to a very localized energy to promote rapid melting and solidification. The observed microstructure is due to very large thermal gradients [ 42 ] and variations in the cooling rate. The selected laser scanning strategy, which was based on alternating layers, produced a typical Y-Z plane microstructure after etching ( Figure 3 a,b) that was made of alternating stripes (of thickness of ≈60 and ≈50 µm) of overlapped semi-circular and curved melting fronts.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, loose powders are removed from the building chamber, and the part is separated from the substrate plate manually or through electrical discharge machining (EDM). Additionally, some SLM machines can pre-heat the substrate plate or the building chamber, which helps to reduce the residual stresses caused by the inherently large thermal gradients caused by the high heating and cooling rates during manufacturing, thereby improving the final part’s quality [ 17 ]. The type of laser wave (continuous or pulsed) can influence the mechanical behavior [ 18 ].…”
Section: Introductionmentioning
confidence: 99%